Chapeau à vous: French-minority Language Teachers’ Pandemic Pedagogies - Cormier, Gail; Burke-Saulnier, Andrea (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2023)
The purpose of this paper was to unpack French-minority language teachers’ perspectives on the impact of the pandemic on their teaching. In fall 2021, semi-structured interviews were conducted virtually with 40 K-12 teachers of French as a minority language in Manitoba and Nova Scotia. While the pandemic has undoubtedly been challenging for language and literacy teachers, many have also developed adaptations and strategies. This paper focuses on those pedagogical accomplishments and teachers’ self-reported moments of success. Three main themes explored were the integration of technology into language teaching, language teacher collaboration and linguistic community building with students.